Synthesis, Structural Determination, Hirshfeld Surface Analysis, 3D Energy Frameworks, Electronic and (Static, Dynamic) NLO Properties of O-Nitroacetanilide (o-NAA): A Combined Experimental and Quantum Chemical Study - Boukabcha, Nourdine; Direm, Amani; Drissi, Mokhtaria; Megrouss, Youcef; Khelloul, Nawel; Dege, Necmi; Chouaih, Abdelkader (Elsevier, 2021)
o-Nitroacetanilide (o-NAA), an organic crystal, was synthesized and fully characterized by means of singlecrystal XRD, FTIR, UV-visible,1H and 13C NMR spectroscopic techniques. Its molecular structure was optimized, the subsequent electronic properties, the spectroscopic spectra were quantified using quantum chemical computations by density functional theory calculations and compared with the experimental results. Furthermore, the Mulliken atomic charges were estimated andthe molecular electrostatic potential map was plotted in order to identify the chemical reactive sites. To study the nonlinear optical (NLO) activity of o-NAA, the electric dipole moment, the static and dynamic polarizability and hyperpolarizabilities were computed indicating that it could be considered as a good candidate for NLO applications. The hydrogen bonding and the non-classical intermolecular interactions were investigated by performing a Hirshfeld surface analysis and their contributions were analyzed via the 2D-Fingerprint plots, thus revealing that the crystal structure of the studied molecule is mainly built up of H...H, H...O/O...H, H...C/C...H and C...O/O...C close contacts. From the 3D-molecular energy frameworks analysis, the lattice energy of the compound was found to be - 95.15 kJ.mol-1, and has exhibited stabilizing strong C-H...O, N-H...C, lp...lp, lp...pi and pi...pi interactions.
Youcef, Megrouss/0000-0002-3823-6911; Nourdine, Boukabcha/0000-0003-1949-6133; Tuna, Murat/0000-0002-8554-903X;
Keywords: NLO Crystal; DFT; Electrostatic Interactions; Hydrogen Bonding; Energy Framework